Organic Balance uterus. - Schiavo, Carlos (2015)
The frequent observation that certain pregnancies of patients with uterine anomalies make an evolution that is unrelated to the existing alteration, made us think that there should be seemingly imponderable factors that are responsible for this unequal development in them.